Przygotowania Okręgu Generalnego Łódź do przejścia na organizację pokojową w 1921 - Jarno, Witold (Acta Universitatis Lodziensis. Folia Historica, 2001)
This article deals with the process of preparations of Łódź General District of the Polish Army for the conversion from the war organisation that obliged in 1921 to the peace time structures. The author highlights as well the process of demobilisation of the military forces on the territory of the District. First the progress of the works aiming at the preparation of the plans of the organisation of the army on a peace footing as well as the conversion of the infantry divisions from the system of two brigades to the system of three regiments (a division was then composed of three infantry regiments instead of four in two brigades like so far) and augmentation of their numbers to thirty was showed. Then there was described the process of demobilisation of the military forces that was inevitable for the adoption of the peace time structure of the army. Due to the lack of the historical sources that issue as far as the Łódź General District is concerned was presented only in general terms. The demobilisation of the 4th and 10th Infantry Division that belonged to the District was the only process considered in a more detailed way. The article is summoned up with the presentation of the general principles of the process of the implementation of the peace time structure of the Polish Army that took place in the autumn 1921 and with the description of all its phases.